CHARACTERISTICS OF PEER FRIENDSHIP (Annual of the Faculty of Philosophy in Skopje, 2013)
The most elementary image of “school-time” is that is the time of meeting, socializing and friendship, bonding and intimate friendships, first love and sympathy. Therefore, friendship, in life of the child and young person is essential, especially for his social and emotional development.In this paper, characteristics of friendship among peers during childhood and adolescence are theoretically processed. More features of friendship are covered as: friendship and development of social skills; friendship and meeting the needs for intimacy; friendship and self image; friendship and the need for companionship; friendship, helping, sharing and cooperation; friendship and emotional safety and friendship; and sense of confidence in the friendship.In this paper are shown the latest findings of theory> and research in this psychological field by researching in the professional literature.
Keywords: FRIENDSHIP; CHARACTERISTICS OF FRIENDSHIP; PEERS; SOCIAL SKILLS; NEED FOR INTIMACY